1990
DOI: 10.3109/00365529008999213
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Colonoscopy

Abstract: In a prospective study involving 833 consecutive outpatient and open-access colonoscopies, attempts were made to characterize the benefit of colonoscopy in terms of both predicted and unpredicted findings and therapeutic procedures. The endoscopist therefore predicted the endoscopic findings before the endoscopy. The results were compared for the different indications for colonoscopy. The overall agreement between the predictions and the colonoscopic findings was 61%. Clinically significant abnormalities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…
Background: Many studies have shown that rectal bleeding is a good indicator of underlying colorectal pathology, and that ost of the lesions in patients presenting with rectal bleeding lie in the left side of the colon [1,5,9,12,23,26]. The recent acceptance of the nurse-practitioner by the National Health Service may allow the use of nurse-endoscopists to develop throughout the United Kingdom.
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
Background: Many studies have shown that rectal bleeding is a good indicator of underlying colorectal pathology, and that ost of the lesions in patients presenting with rectal bleeding lie in the left side of the colon [1,5,9,12,23,26]. The recent acceptance of the nurse-practitioner by the National Health Service may allow the use of nurse-endoscopists to develop throughout the United Kingdom.
…”
mentioning
confidence: 99%
“…A nurse-led OAFS is safe, effective, and acceptable to patients. It also is more cost effective than a consultantled service.Many studies [5,9,12,23,26] have shown rectal bleeding to be a good indicator of underlying colorectal pathology. It is well documented that most significant colorectal lesions are left-sided.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Colonoscopy is more precise than radiology for detecting diseased mucosa because of the direct visualization of the mucosa and the possibility of taking biopsies during the procedure [23,24]. The role of colonoscopy in UC has been further substantiated with the increasing use of endoscopic endpoints for documentation of remission and response to therapy.…”
Section: Discussionmentioning
confidence: 98%
“…A variety of factors have been linked to the development of adenomas or CRC (21)(22)(23)(24)(25), but currently there is no dominant risk factor that could be practically used for risk stratification in screening for neoplasia among average risk adults without known family history of CRC. Abdominal symptoms with no evidence of bleeding have been considered a poor indication for colonoscopy in series with small numbers of patients (26)(27)(28)(29). Clarification of the relative impact of these and other variables on the risk of advanced adenomas in average risk persons is needed, because such clarification might provide basis to design more efficient CRC screening strategies.…”
Section: Introductionmentioning
confidence: 99%